(3SjQI QShd Gddg Udi Gddg Ydjg hSdes - (3GHf gTGe , YHO Gdedc Hf gTGe Hf GjhH GdMejQj GdeYGaQj, LeGd GdOjf CHh eMeO,J (B213 (3g` s
(3ChdgG (B:s
(3ZRhI GdShjb bGd GHf gTGe Ke ZRd CHh SajGf Hf MQH ZRhI GdShja ai Pi GdMLI s
(3BNQgG (B:s
(3Cde Jbd jG QShd Gddg Efc JONd ecI BefG bGd (B: (3Hdi , CabdJ dce ef YGei gPG ? bGdhG (B: (3dG bGd (B: (3agh ceG bGd di LHQjd Udi Gddg Ydjg hSde s
(3GdfSNI HgG MhGTs
(3QhGgG YHO GdQMje heMeO hCMeO CHfGA YHO Gddg Hf YHO GdQMje Hf SYjO Hf CHj RQYI GdRgQi GdHQbis
(3HBNQgG bQGAI Ydi CHj HcQ eMeO Hf CMeO Hf WGgQ GdbjSis
(3fSNI KGfjI Ydi Qb ZRGd s
(3JHUQI GdYfhGf (B:s
(3JaSjQ s
Keywords: (3GdJGQjNs